2002
DOI: 10.1002/1521-396x(200206)191:2<548::aid-pssa548>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity of MgB2 after Mechanical Milling

Abstract: A MgB 2 powder was mechanically milled for different times. X-ray diffraction indicated the formation of an intermediate phase with an unknown structure before formation of amorphous phase. The intermediate structure was superconducting below 18 K, while the amorphous phase was nonsuperconducting till 4.2 K. After heat treatment at 700 C, all the mechanically milled samples formed back into the hexagonal MgB 2 structure with T c ¼ 39 K. X-ray and Raman investigations suggested that the intermediate structure w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
10
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 23 publications
3
10
1
Order By: Relevance
“…MgB 4 was not detected in every spectrum, while measurable levels of MgO were observed in all spectra. In contrast to this work, Gao et al [32] observed complete amorphization of MgB 2 powder after 20 h milling in air with steel balls, demonstrated by the disappearance of crystalline peaks in the -2 XRD spectrum with increasing milling time, indicating that the milling methods used by different research groups should not necessarily be expected to produce similar powders, even when milling durations are identical. Previously we reported a correlation between density and hardness for MgB 2 samples over a wide range of both variables [33].…”
Section: Magnesium Diboride Produced From Modified Powderscontrasting
confidence: 86%
“…MgB 4 was not detected in every spectrum, while measurable levels of MgO were observed in all spectra. In contrast to this work, Gao et al [32] observed complete amorphization of MgB 2 powder after 20 h milling in air with steel balls, demonstrated by the disappearance of crystalline peaks in the -2 XRD spectrum with increasing milling time, indicating that the milling methods used by different research groups should not necessarily be expected to produce similar powders, even when milling durations are identical. Previously we reported a correlation between density and hardness for MgB 2 samples over a wide range of both variables [33].…”
Section: Magnesium Diboride Produced From Modified Powderscontrasting
confidence: 86%
“…Since the as-milled MgB 2 also exhibits the large changes of the diamagnetization at both 39 K and about 8 K, it is considered that such mechanically milled MgB 2 consists of at least two phases: crystalline and disordered MgB 2 . Gao et al [3] studied the effect of mechanical milling on the structure of MgB 2 and its superconductivity using a vibrated Spex 8000 Mixer Mill, and reported similar changes of superconductivity of MgB 2 by mechanical milling. They suggested that mechanical milling led to formation of an ''intermediate structure'' characterized by an additional peak of the XRD patterns and that this structure exhibited superconductivity at 18 K. In our case, there is no additional peak in the XRD patterns for all samples.…”
supporting
confidence: 87%
“…These suggest that such small difference of structural disorder brings superconductivity at T a2 . T a2 is hardly influenced by periods of annealing at 550 C and by annealing even at 650 C. Therefore, new superconducting phase below T a2 is relatively stable on the annealing process up to 650 C. On the other hand,the disordered MgB 2 restores completely superconductivity at T c ¼ 39 K after annealing at 700 C [3,4]. Thus, the present study has reported the superconducting feature on the annealing process of the disordered MgB 2 at lower temperature below 650 C. …”
supporting
confidence: 59%
See 1 more Smart Citation
“…Lorenz et al [47] also report that the value of T c is degraded with increasing lattice strain, a result confirmed by Serquis et al [49]. T c in MgB 2 has also been found to be lowered following mechanical milling [50] and after irradiation by fast neutrons [51]. In contrast to the work of Lorenz et al [47] and Serquis et al [49], Hinks et al [38] have recently reported that accidental impurity doping can have an effect on T c much larger than that of lattice strain.…”
Section: Intrinsic Dependence Of T C On Pressurementioning
confidence: 86%